Strategi Pemasaran Bank BCA dalam Menciptakan Nilai Kepuasan dan Loyalitas Pelanggan - Santia Omike Bunga; Hendra Riofita (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This research aims to analyze Bank BCA's marketing strategy in creating customer satisfaction and loyalty values ​​amidst intense banking industry competition. The method used is a literature review which involves analysis of various reference sources, including articles, books and previous research reports, to understand the implementation of effective marketing strategies. The research results show that Bank BCA has succeeded in improving the bank's image through improving service quality, digital product innovation and attractive promotions. Additionally, a responsive complaint mechanism helps in identifying areas of improvement to increase customer satisfaction. In conclusion, through an integrated approach to marketing, Bank BCA not only meets customer expectations but also builds long-term loyalty, thereby maintaining a competitive position in the market.   Keywords: Marketing Strategy; Bank BCA ; Satisfaction ; and Loyalty